Pembelajaran bahasa arab berbasis teknologi digital - Z, Putri Retavia (Maliki Interdisciplinary Journal, 2025)
As digital technology advances, Arabic language learning methods have seen significant changes. The incorporation of technology in Arabic language education presents valuable opportunities to boost students' language skills through interactive media, online applications, and technology-driven learning platforms. This article examines the application of digital technology in Arabic learning, highlighting its benefits and the challenges encountered. By employing a literature review method and analyzing the implementation of technology in language learning, the research findings indicate that technology can enhance learning motivation, ease access to materials, and allow for personalized learning experiences. Thus, innovation and appropriate strategies are essential for integrating technology into the Arabic language education curriculum. To optimize the benefits of technology in Arabic language learning, an appropriate implementation strategy is needed. Educational institutions must be more proactive in developing technology-based learning systems and providing training for teachers so that they can use it optimally.